(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper the concept of fuzzy bipolar metric spaces are investigated and their properties in relation with fixed points by the consideration of triangular property of fuzzy bipolar metric are explored. The study presents a series of established results under covariant and contravariant mappings supported by illustrative examples and discusses the implications of these findings. Furthermore, the established results are applied to demonstrate the existence and uniqueness of solutions to nonlinear integral equations. The exploration of fuzzy bipolar metric spaces and their application to integral equations provides valuable insights into the field of mathematical analysis and opens avenues for further research.